2017
DOI: 10.1371/journal.pone.0182125
|View full text |Cite
|
Sign up to set email alerts
|

Breast conservation surgery versus total mastectomy among women with localized breast cancer in Soweto, South Africa

Abstract: PurposeBreast conserving surgery (BCS) has become the preferred surgical option for the management of patients with nonmetastatic breast cancer in high-income countries. However, little is known about the distribution and determinants of BCS in low-and middle-income countries, especially those with high HIV prevalence.MethodsWe compared demographic and clinical characteristics of female patients who received BCS and those who received total mastectomy (TM) for nonmetastatic invasive carcinoma of the breast in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 27 publications
1
18
0
2
Order By: Relevance
“…21 Non-mutilating options of breast conserving therapy, have historically played a minor role in poorly resourced settings. 18 In part, choosing mastectomy may reflect the delays and transport problems that emerge in a 6-week course of daily radiation that is currently mandatory for SABC study-which often is a difficult decision for surgeons and their patients. Recognizing the structural and social complexities through which people navigate illness and treatment is imperative when thinking about the social and cultural ramification around intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Non-mutilating options of breast conserving therapy, have historically played a minor role in poorly resourced settings. 18 In part, choosing mastectomy may reflect the delays and transport problems that emerge in a 6-week course of daily radiation that is currently mandatory for SABC study-which often is a difficult decision for surgeons and their patients. Recognizing the structural and social complexities through which people navigate illness and treatment is imperative when thinking about the social and cultural ramification around intervention.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 17 Total mastectomy remains the most common surgical treatment today in South African public health services, despite breast conserving surgery being the surgical treatment of choice in high-resource settings. 18 Education around breast cancer prognosis and treatment and the fear of mastectomy and chemotherapy impede women from care-seeking, 10 in part, because these treatments frequently cause significant side effects and are associated with emotional distress and trauma. 18 , 19 Many women experience stress associated with physical mutilation of the body, emotional distress associated with a cancer diagnosis and treatments, and lingering depressive symptoms, particularly when women depend on an underfunded public sector where psychological support services are limited or non-existent.…”
Section: Introductionmentioning
confidence: 99%
“…As we have previously discussed, further study is needed to elucidate objective and pathological response rates and the extent to which NACT may facilitate BCS as opposed to mastectomy in our patient population. 38 …”
Section: Discussionmentioning
confidence: 99%
“…7 Breast conservation therapy (BCT) is comprised of lumpectomy, axillary lymph node evaluation, and adjuvant radiation therapy and is considered an efficient alternative to mastectomy for early-stage breast carcinoma. [8][9][10] Long-term follow-up studies have reported that radical mastectomy does not offer an advantage in disease outcomes for early-stage breast cancer patients compared with BCT and other less extensive surgeries. [11][12][13][14][15][16] Furthermore, compared with mastectomy, breastconserving surgery (BCS) causes less physical disfigurement and psychological trauma.…”
Section: Introductionmentioning
confidence: 99%
“…Regional excision may not be the cure for cancer . Breast conservation therapy (BCT) is comprised of lumpectomy, axillary lymph node evaluation, and adjuvant radiation therapy and is considered an efficient alternative to mastectomy for early‐stage breast carcinoma . Long‐term follow‐up studies have reported that radical mastectomy does not offer an advantage in disease outcomes for early‐stage breast cancer patients compared with BCT and other less extensive surgeries .…”
Section: Introductionmentioning
confidence: 99%